Analitis Geovisual Okupansi Halte dan Pergerakan Penumpang Transjakarta - Alian Fathira Khomani; Trias Aditya (Universitas Gadjah Mada, 2020)
Public eagerness to use Transjakarta as a transport mode has been increasing over the past few years as the ridership growth consistently. To keep the growth up, stakeholders need to understand the passenger behavior by creating an effective operational system so that the passenger satisfaction maintained. An understanding of passenger behavior can be obtained by identifying its pattern and trend which recorded as passenger transaction data. This project uses passenger transaction data which contains information about time and space to produce interactive visualization as a means to identify passenger behavior. Interactive visualization created in this project depicts the trend of bus stop occupancy and passenger movement from one stop to another. The visualization consists of a map and diagrams which relate to each other as one integrated analytical dashboard system. The visualization design process combines Tableau 2019.2 and Mapbox GL JS to create powerful visualization supported by a 3D map view that facilitates analytical reasoning work. Geovisual analytics dashboard as a result of this project is intended for PT. Transportasi Jakarta staff to make decisions. Some staff was asked to examine the usability of the dashboard regarding its effectiveness, efficiency, and accessibility aspects. The usability test pointed out that the analytical dashboard can generate new information about the patterns and trends of Transjakarta passengers.